COVID‐19 in kidney transplant recipients. Issue 7 (27th May 2020) - Nair, Vinay; Jandovitz, Nicholas; Hirsch, Jamie S.; Nair, Gayatri; Abate, Mersema; Bhaskaran, Madhu; Grodstein, Elliot; Berlinrut, Ilan; Hirschwerk, David; Cohen, Stuart L.; Davidson, Karina W.; Dominello, Andrew J.; et al.
Abstract : There is minimal information on coronavirus disease 2019 (COVID‐19) in immunocompromised individuals. We have studied 10 patients treated at 12 adult care hospitals. Ten kidney transplant recipients tested positive for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) by polymerase chain reaction, and 9 were admitted. The median age was 57 (interquartile range [IQR] 47‐67), 60% were male, 40% Caucasian, and 30% Black/African American. Median time from transplant to COVID‐19 testing was 2822 days (IQR 1272‐4592). The most common symptom was fever, followed by cough, myalgia, chills, and fatigue. The most common chest X‐ray and computed tomography abnormality was multifocal patchy opacities. Three patients had no abnormal findings. Leukopenia was seen in 20% of patients, and allograft function was stable in 50% of patients. Nine patients were on tacrolimus and a mycophenolic antimetabolite, and 70% were on prednisone. Hospitalized patients had their antimetabolite agent stopped. All hospitalized patients received hydroxychloroquine and azithromycin. Three patients died (30%), and 5 (50%) developed acute kidney injury. Kidney transplant recipients infected with COVID‐19 should be monitored closely in the setting of lowered immunosuppression. Most individuals required hospitalization and presenting symptoms were similar to those of nontransplant individuals. Abstract : In this series of 10 kidney transplant recipients with COVID‐19, most patients presented with symptoms similar to those of the nontransplant population, 9 required hospitalization and were treated with reduction of immunosuppression, and there was a 50% incidence of acute kidney injury and a 30% mortality.